Analisis Pendapatan dan Saluran Pemasaran Usahatani Bayam di Dusun III Pulau Semambu Kecamatan Idralaya Utara Kabupaten Ogan Ilir Sumatera Selatan - Saputra, Ananda (Universitas Bojonegoro, 2024)
The purposes of this research are to analyze Income Analysis and Marketing Channel of Spinach Business in Semambu Island Village, North Indralaya District, Ogan Ilir Regency, South Sumatera. The method used survey method and sampling method using proportional stratified random sampling.. The study took 30 sample out of 550 farmers. The data were processed by tabulation and continued with Spearman correlation test and analyzed descriptively. Based on first goal, the the role of farmer groups on utilization of subsidized fertilizer in Banyu Urip Village Tanjung Lago Subdistrict Banyuasin Regency was included in the high category with an average score of 28,97 (score range 28,01 < x ≤ 36,00). On second goal, the income of paddy farmer in Banyu Urip Village were in an average Rp.58.113.333 per cultivated area in a year or Rp. 30.745.889 per ha in a year. On third goal, based on the calculation of rank Spearman correalation obtained there were correlation between the role of farmer gruoups and paddy farmer income.